2021
DOI: 10.3389/fmats.2021.624631
|View full text |Cite
|
Sign up to set email alerts
|

When Beneficial Biofilm on Materials Is Needed: Electrostatic Attachment of Living Bacterial Cells Induces Biofilm Formation

Abstract: Bacterial attachment is crucial in many biotechnological applications, but many important bacterial strains cannot form biofilms. Biofilms can damage materials, and current strategies to manage biofilms are focused on inhibition and removal of biofilm. Biofilm formation is inevitable when materials are exposed to microbes and instead of biofilm prevention, we propose management of microbial composition by formation of biofilms with beneficial microbes. Since bacteria need to overcome a high repulsive force to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…In another study, altered EPS mutants of B. japonicum 2143 also had no effect on the nodule formation ability of the host (Karr et al, 2000 ). Along with the role of EPS, other bacterial biofilm formation-inducing factors have been reported, such as electrostatic forces and flagella (Rinaudi and Giordano, 2010 ; Deev et al, 2021 ). Lectin-binding data also showed phenotypic plasticity as each RECC had its own lectin-binding barcode profile.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, altered EPS mutants of B. japonicum 2143 also had no effect on the nodule formation ability of the host (Karr et al, 2000 ). Along with the role of EPS, other bacterial biofilm formation-inducing factors have been reported, such as electrostatic forces and flagella (Rinaudi and Giordano, 2010 ; Deev et al, 2021 ). Lectin-binding data also showed phenotypic plasticity as each RECC had its own lectin-binding barcode profile.…”
Section: Discussionmentioning
confidence: 99%
“…PEI used in this study showed no toxic effects (see Figure 1E and Rybkin et al, 2019 ; van Tatenhove-Pel et al, 2021 ), but it might be toxic if other therapeutically relevant bacteria are used. However, there have been demonstrated approaches to change or modify toxic PEI (see Deev et al, 2021 ), which indicate that the toxicity must be determined in beforehand the LbL is applied for the selected strains.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm establishment of a surface is often a consequence of a material being inhabited by microbes for a prolonged period [20]. While frequent application of sanitizer on surfaces can greatly reduce the probability of such occurrence, there is still a chance for microbial attachment and biofilm formation on the surface.…”
Section: Anti-biofilm Functionality Of Sanitizersmentioning
confidence: 99%